Sectoral shocks and spillovers - Das, Sonali,Magistretti, Giacomo,Pugacheva, Evgenia,Wingender, Philippe (International Monetary Fund, 2021)
This paper examines the role of sectoral spillovers in propagating sectoral shocks in the broader economy, both in the past and during the COVID-19 pandemic. In particular, we study how shocks that occur within a sector itself and spillovers from shocks to other sectors affect sectoral activity, for a large sample of countries from 1995 to 2014. We find that both supply and demand shocks-measured as changes in, respectively, productivity and government purchases at the sector level-have large spillover effects on sector-level gross value added and on a sector's share of the economy. We then use these historical estimates, together with the network structure of global production, to quantify the spillovers from the economic shock associated with the pandemic. We find spillover effects to be sizeable, making up a significant fraction of the overall decline in activity in 2020.Our results have implications for the design of policies with a sectoral dimension
10.5089/9781513587394.001
Keywords: Graue Literatur; Production networks; input-output tables; sectoral shocks; General Equilibrium and Disequilibrium; Macroeconomic Aspects of International Trade and Finance; spillovers; COVID-19; Business Fluctuations; Cycles; Externalities; Production and Operations Management; General Equilibrium and Disequilibrium: Input-Output Tables and Analysis; Diseases: Contagious; Economic Theory; Macroeconomic Aspects of International Trade and Finance: General; Public Finance; Health Behavior; Agriculture: Aggregate Supply and Demand Analysis; Prices; National Government Expenditures and Related Policies: General; Cost; Capital and Total Factor Productivity; Capacity; Economic & financial crises & disasters; Economics of specific sectors; Infectious & contagious diseases; Economic theory & philosophy; Public finance & taxation; Macroeconomics; Financial sector policy and analysis; Economics: General; Health; Supply shocks; Economic theory; Expenditure; Total factor productivity; Production; Currency crises; Informal sector; Economics; International finance; Communicable diseases; Supply and demand; Expenditures; Public; Industrial productivity